Reflections of breastfeeding on infant oral health and maternal reality: a narrative review (Research, Society and Development, 2021)
Breastfeeding is the wisest natural bonding, affection, protection and nutrition strategy for the child and the mother, and this practice has a key role in healthy development, bringing countless benefits. In this context, the World Health Organization recommends exclusive breastfeeding for approximately 6 months, when this period of six months is not obeyed, the child is more likely to acquire functional alterations. Based on this, this article proposes, through an analysis of the existing literature, clarifying information on the importance and need for breastfeeding and its effects on the child's stomatognathic system, its benefits on the general health of the mother-infant binomial, and the disadvantages in the absence of this practice, with early weaning being an obstacle in the individual's life and consequently there is an installation of harmful habits, and with that, the deprivation of breastfeeding later can bring problems such as malocclusion development, changes in bone growth, breathing mouth, and abnormal tongue functions during swallowing, phonation and posture.